Perlindungan Hukum terhadap Pemegang Hak Atas Tanah yang di Tetapkan Sebagai Tanah Terlantar - Indra Rusdian Lego (Peneliti.net, 2020)
The purpose of this study is the legal protection of land rights holders that are designated as abandoned land. The problem in this research is how is the practice of determining abandoned land by the National Land Agency? and What is the form of legal protection for holders of land rights that are designated as abandoned land? The research method used is a normative juridical research method that is supported by library data. Based on the results of the analysis, BPN has to determine abandoned land. BPN has the authority to determine abandoned land in accordance with the theory of authority in the form of delegation from the government (President) to BPN as regulated in Article 17 PP No.11 of 2010. Land designated as abandoned land by BPN does not receive protection in the form of compensation compensation because it is not regulated in Government Regulation Number 11 of 2010 concerning Control and Utilization of Abandoned Lands because the legal relationship of abandoned land owners, their rights to the land are abolished, their legal relations are terminated and confirmed to be land directly controlled by the state and then to the former Rightsholders are given back the part of the land that is really cultivated, used and utilized in accordance with the decision to grant rights. In order to obtain land rights that have been designated as abandoned land, the right holder can apply for land rights in accordance with the provisions of statutory regulations. Before deciding and determining land that is indicated as abandoned land, it must be done with the correct mechanism and procedure.